1978
DOI: 10.1017/s0079497x00010082
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Deverel-Rimbury Pottery from Cranbourne Chase

Abstract: Pitt Rivers' excavations in Cranbourne Chase not only provided his successors with a lavish series of reports but also with a remarkable body of artefacts. These finds are now housed in the Salisbury and South Wiltshire Museum. The research programme which is centred upon the re-excavation of South Lodge Camp will include a new assessment of the Bronze Age material in this collection. This work discussed here is the first stage in this project (cf. Barrett and Bradley 1978).The Bronze Age sites investigated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
1983
1983

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Pottery comes from settlements and cemeteries, and both exist in close proximity. Those vessels which were selected to accompany the ashes of the dead were drawn directly from the domestic repertoire, a point demonstrable at South Lodge Camp, Wiltshire (Barrett et al 1978) and Itford Hill, Sussex (Ellison in Holden 1972). In her recent discussion of the ceramics Ellison (1980a) has refined previous categories and presented the material as a tripartite hierarchy of fine wares, everyday wares and heavy duty wares similar in form to that suggested for Beaker assemblages by Clarke (1976).…”
Section: The Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pottery comes from settlements and cemeteries, and both exist in close proximity. Those vessels which were selected to accompany the ashes of the dead were drawn directly from the domestic repertoire, a point demonstrable at South Lodge Camp, Wiltshire (Barrett et al 1978) and Itford Hill, Sussex (Ellison in Holden 1972). In her recent discussion of the ceramics Ellison (1980a) has refined previous categories and presented the material as a tripartite hierarchy of fine wares, everyday wares and heavy duty wares similar in form to that suggested for Beaker assemblages by Clarke (1976).…”
Section: The Ceramicsmentioning
confidence: 99%
“…The situation is more complex when the bucket urns are brought into account, for Ellison has shown that a number of these types may occur in a particular region whilst other distributions cut across the regional assemblages which she has defined. A recent study of Deverel-Rimbury fabrics from Cranborne Chase has indicated that fine ware vessels share a common clay source, whilst the sharing of a number of clay sources for bucket urn production also occurred (Barrett et al 1978).…”
Section: Ceramic Organisationmentioning
confidence: 99%
“…These mounds were located close to, but behind, the enclosure, a position which recalls the relationship between cemetery and settlement at Itford Hill in Sussex (Holden, 1972). The pottery in the Barrow Pleck cemetery was in the same fabric as that in the nearby settlement and suggests a comparable pattern (Barrett, Bradley, Cleal and Pike, 1978).…”
Section: I-c-e Reading Bedsmentioning
confidence: 74%
“…The General was the first person to suggest a direct link between South Lodge Camp and the Barrow Pleck cemetery, and this impression appears to be confirmed by Neutron Activation Analysis of pottery from these two parts of the site (Barrett, Bradley, Cleal & Pike, 1978, and further work since that time). As we have seen, there were originally six barrows in this cemetery, but two of these were probably in use before the field system developed, although each contained at least one Deverel-Rimbury deposit.…”
Section: Fig 4 Outlineplan Of the Barrow Pleck Cemetery Showing Tmentioning
confidence: 87%